Diagenesis and Fluid Flow Variability of Structural Heterogeneity Units in Tight Sandstone Carrier Beds of Dibei, Eastern Kuqa Depression. (10th January 2017) - Shi, H.; Luo, X. R.; Lei, G. L.; Zhang, L. Q.; Zhang, L. K.; Lei, Y. H.
Abstract : Tight sand gas plays an important role in the supply of natural gas production. It has significance for predicting sweet spots to recognize the characteristics and forming of heterogeneity in tight sandstone carrier beds. Heterogeneity responsible for spatial structure, such as the combination and distribution of relatively homogeneous rock layers, is basically established by deposition and eodiagenesis that collectively affect the mesogenesis. We have investigated the structural heterogeneity units by petrofacies in tight sandstone carrier beds of Dibei, eastern Kuqa Depression, according to core, logging, and micropetrology. There are four types of main petrofacies, that is, tight compacted, tight carbonate-cemented, gas-bearing, and water-bearing sandstones. The brine-rock-hydrocarbon diagenesis changes of different heterogeneity structural units have been determined according to the pore bitumen, hydrocarbon inclusions, and quantitative grain fluorescence. Ductile grains or eogenetic calcite cements destroy the reservoir quality of tight compacted or tight carbonate-cemented sandstones. Rigid grains can resist mechanical compaction and oil emplacement before gas charging can inhibit diagenesis to preserve reservoir property of other sandstones. We propose that there is an inheritance relationship between the late gas and early oil migration pathways, which implies that the sweet spots develop in the reservoirs that experienced early oil emplacement.